2019
DOI: 10.32598/jams.22.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Antibiofilm Properties of Satureja Essential Oil Against Periodontal Pathogens

Abstract: Background and Aim Periodontal diseases are among the most prevalent inflammatory diseases caused by oral bacteria. Expansion of oral biofilm causes various diseases such as gingival inflammation and periodontitis. The Satureja plant has various species, all of which are aromatic. This plant is traditionally used for the treatment of some diseases. The present study was conducted to evaluate the effect of Satureja essential oil on periodontal pathogens. Methods and Materials In this study, we evaluated four pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For Enterococcusfaecalis, Streptococcussanguis, Eikenellacorrodens, Actinomycesviscose were 562.1, 562.1, 39.0, 562.1 μg/ml respectively (8) .…”
Section: Satureja Sppmentioning
confidence: 92%
See 1 more Smart Citation
“…For Enterococcusfaecalis, Streptococcussanguis, Eikenellacorrodens, Actinomycesviscose were 562.1, 562.1, 39.0, 562.1 μg/ml respectively (8) .…”
Section: Satureja Sppmentioning
confidence: 92%
“…So that their stems, leaves and roots have been used (5) . Studies have shown that many native plants of Iran such as Salvia officinalis, Satureja have anti-tooth decay capabilities (6)(7)(8) . It has also been shown to have antimicrobial activity against oral microbes due to the presence of a wide range of metabolites such as flavonoids, polyphenols, terpenes, alkaloids and alcoholic sugars such as xylitol, which are then used in the treatment and control of tooth decay (9) .…”
Section: Introductionmentioning
confidence: 99%